2018
DOI: 10.1016/j.epsl.2018.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the global distribution of contourite drifts: Insights from an eddy-resolving ocean model

Abstract: Contourite drifts are anomalously high sediment accumulations that form due to reworking by bottom currents. Due to the lack of a comprehensive contourite database, the link between vigorous bottom water activity and drift occurrence has yet to be demonstrated on a global scale. Using an eddyresolving ocean model and a new georeferenced database of 267 contourites, we show that the global distribution of modern contourite drifts strongly depends on the configuration of the world's most powerful bottom currents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 55 publications
0
48
0
Order By: Relevance
“…events of strong currents capable of eroding the seafloor and generating benthic nepheloid layers) in areas with high sea-surface eddy kinetic energy, related to the Gulf Stream or its associated rings. The importance of eddies in controlling deep-sea sedimentation is also supported by a global comparison of contourite distribution and hydrodynamic modelling, which showed that contourites are located in areas with high simulated bottom eddy kinetic energy (Thran et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 78%
See 1 more Smart Citation
“…events of strong currents capable of eroding the seafloor and generating benthic nepheloid layers) in areas with high sea-surface eddy kinetic energy, related to the Gulf Stream or its associated rings. The importance of eddies in controlling deep-sea sedimentation is also supported by a global comparison of contourite distribution and hydrodynamic modelling, which showed that contourites are located in areas with high simulated bottom eddy kinetic energy (Thran et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 78%
“…Bottom currents are often considered as permanent steady flows, in contrast to the more episodic nature of gravity-flows (Rebesco et al, 2014). Nevertheless, both short-term and seasonal variations may also be involved in controlling the formation of sediment drifts (Zhang et al, 2016;Thran et al, 2018). More studies based on in situ current measurements and hydrodynamic modelling are needed to better understand the intensity and variability of bottom currents and their effect on deep-sea sedimentation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Sedimentary facies and architecture of the hybrid turbidite-drift channel systems are therefore controlled by the frequency of sediment gravity flow activity and the relative persistence and strength of bottom currents. Deposit modification would mostly occur during periods when bottom currents dominate; during this time, the strength and character or direction of the bottom current system would be variable due to, for example, seasonal eddies and benthic storms (Thran et al, 2018;Miramontes, et al, 2019). However, changes in sediment flux (i.e., frequency of sediment gravity flows) and fluctuation of bottom currents over geological time scales (10 6 m.y.)…”
Section: A Model For Temporally Variable Bottom-current Interaction Wmentioning
confidence: 99%
“…The contourite drifts were discovered about 50 years ago [7]. They are defined as sedimentary bodies formed under the influence of the system of the along-slope near-bottom currents, so contourite drifts are usually investigated to reconstruct near-bottom paleocurrents speed [8][9][10][11]. In the North Atlantic, the contourite drifts have been formed due to the inflow of deep Arctic waters with bottom currents, the speed of which was increased during warming and decreased during glaciation [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%